KRAS exon 2 mutations influence activity of regorafenib in an SW48-based disease model of colorectal cancer. (July 2015) - Camaj, Peter; Primo, Stefano; Wang, Yan; Heinemann, Volker; Zhao, Yue; Laubender, Ruediger Paul; Stintzing, Sebastian; Giessen-Jung, Clemens; Jung, Andreas; Gamba, Sebastian; Bruns, Christiane Josephine; Modest, Dominik Paul
ABSTRACT : Aim: To investigate the impact of KRAS mutation variants on the activity of regorafenib in SW48 colorectal cancer cells.Materials & methods: Activity of regorafenib was evaluated in isogenic SW48 KRAS wild-type (WT) and mutant cells. Subcutaneous xenografts ( KRAS WT and G12C mutant variants) in NOD/SCID mice were analyzed to elucidate the effect of regorafenib treatment in vivo .Results: Compared with KRAS WT cells, all mutant variants seemed associated with some degree of resistance to regorafenib-treatment in vitro. In vivo, activation of apoptosis (TUNEL) and reduction of proliferation (Ki67) after treatment with regorafenib were more pronounced in KRAS WT tumors as compared with G12C variants.Conclusion: In SW48 cells, exon 2 mutations of the KRAS gene may influence antitumor effects of regorafenib.